1999
DOI: 10.1074/jbc.274.11.7067
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of the Pit-2 Phosphate Transporter/Retrovirus Receptor by Protein Kinase C ε

Abstract: The membrane receptors for the gibbon ape leukemia retrovirus and the amphotropic murine retrovirus serve normal cellular functions as sodium-dependent phosphate transporters (Pit-1 and Pit-2, respectively). Our earlier studies established that activation of protein kinase C (PKC) by treatment of cells with phorbol 12-myristate 13-acetate (PMA) enhanced sodium-dependent phosphate (Na/P i ) uptake. Studies now have been carried out to determine which type of Na/P i transporter (Pit-1 or Pit-2) is regulated by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
(35 reference statements)
2
25
0
Order By: Relevance
“…Likewise, treatment with the PKC inhibitors GF109202X and Gö6976, or with the PKC activator PMA, did not affect GALV envelope protein-induced cell-cell fusion. These results are in agreement with our earlier studies, which showed that P i uptake mediated by PiT2, but not by PiT1, is up-regulated with exposure of cells to PMA (17). Of interest is the finding that the protein kinase inhibitor Rottlerin significantly decreased GALV envelope protein-induced cell-cell fusion (Table V).…”
Section: Syncytium Formation Induced By Galv Envelope Protein In Nih3supporting
confidence: 82%
See 4 more Smart Citations
“…Likewise, treatment with the PKC inhibitors GF109202X and Gö6976, or with the PKC activator PMA, did not affect GALV envelope protein-induced cell-cell fusion. These results are in agreement with our earlier studies, which showed that P i uptake mediated by PiT2, but not by PiT1, is up-regulated with exposure of cells to PMA (17). Of interest is the finding that the protein kinase inhibitor Rottlerin significantly decreased GALV envelope protein-induced cell-cell fusion (Table V).…”
Section: Syncytium Formation Induced By Galv Envelope Protein In Nih3supporting
confidence: 82%
“…Stimulation of A-MuLV Envelope Protein-induced Syncytium Formation by PKC-In earlier studies, it was established that activation of PKC by treatment of cells with PMA increased PiT2-mediated P i uptake, and that this effect was mediated through PMA activation of the PKC⑀ isoform (17). Thus, studies were initiated to determine if PKC⑀ also was involved in mediating A-MuLV envelope-induced cell-cell fusion.…”
Section: Inhibition Of A-mulv Envelope Protein-induced Syncytiummentioning
confidence: 99%
See 3 more Smart Citations